In situ analysis of denitrifying toluene- and m-xylene-degrading bacteria in a diesel fuel-contaminated laboratory aquifer column. - Hess, A (1997)
A diesel fuel-contaminated aquifer was bioremediated in situ by the injection of oxidants (O2 and NO3-) and nutrients in order to stimulate microbial activity. After 3.5 years of remediation, an aquifer sample was excavated and the material was used (i) to isolate bacterial strains able to grow on selected hydrocarbons under denitrifying conditions and (ii) to construct a laboratory aquifer column in order to simulate the aerobic and denitrifying remediation processes. Five bacterial strains isolated from the aquifer sample were able to grow on toluene (strains T2 to T4, T6, and T10), and nine bacterial strains grew on toluene and m-xylene (strains M3 to M7 and M9 to M12). Strains T2 to T4, T6, and T10 were cocci, and strains M3 to M7 and M9 to M12 were rods. The morphological and physiological differences were also reflected in small sequence variabilities in domain III of the 23S rRNA and in the 16S rRNA. Comparative sequence analyses of the 16S rRNA of one isolate (T3 and M3) of each group revealed a close phylogenetic relationship for both groups of isolates to organisms of the genus Azoarcus. Two 16S rRNA-targeted oligonucleotide probes (Azo644 and Azo1251) targeting the experimental isolates, bacteria of the Azoarcus tolulyticus group, and Azoarcus evansii were used to investigate the significance of hydrocarbon-degrading Azoarcus spp. in the laboratory aquifer column. The number of bacteria in the column determined after DAPI (4',6-diamidino-2-phenylindole) staining was 5.8 x 10(8) to 1.1 x 10(9) cells g of aquifer material-1. About 1% (in the anaerobic zone of the column) to 2% (in the aerobic zone of the column) of these bacteria were detectable by using a combination of probes Azo644 and Azo1251, demonstrating that hydrocarbon-degrading Azoarcus spp. are significant members of the indigenous microbiota. More than 90% of the total number of bacteria were detectable by using probes targeting higher phylogenetic groups. Approximately 80% of these bacteria belonged to the beta subdivision of the class Proteobacteria (beta-Proteobacteria), and 10 to 16% belonged to the gamma-Proteobacteria. Bacteria of the alpha-Proteobacteria were present in high numbers (10%) only in the aerobic zone of the column.